Fundamentals of Information and Communication Technologies - Chen, Shun-Ping (Cambridge Scholars Publisher, 2020)
This book covers the basic issues and principles of information and communication technologies. It explains the key theories, techniques and applications of this field for both academic and professional audiences. Beginning with an overview of information and communication networks and architecture, the text explores information theory, coding and modulation schemes, wave propagation, wireless and wireline communications, network security, network management, network planning and optimisation methods for digital communication networks.